Incidencia del parasitoide Calliephialtes grapholithae Cresson (Hymenoptera: Ichneumonidae) en larvas de Cydia caryana Fitch (Lepidoptera: Tortricidae) - Bautista-Martínez, Néstor; Illescas-Riquelme, Carlos Patricio; Ramos-Martínez, José Antonio; Ruiz-Cancino, Enrique (Instituto de Ecología, A.C., 2018)
In the present work, the association between the parasitoid Calliephialtes grapholithae and larvae of Cydia caryana is reported. Pecan nuts collections were made in the area of Jaumave, Tamaulipas, later the fruits were confined in plastic containers to wait for the emergence of adults. Another hymenopteran that emerged in the study was Eupelmus sp., its association could not be confirmed since it can be conferred as a parasitoid or hyperparasitoid.